Sexual debut in young adults in Cali as transition: keys for care - Claudia Patricia Valencia Molina; Gladys Eugenia Canaval Erazo; Teresita María Sevilla Peñuela; Linda Teresa Orcasita Pineda (Universidad de Antioquia, 2015)
Objectives. This work sought to understand sexual debut as a transitional process in the lives of a group of young adults and to interpret the meaning of this transition for them. Methodology. This was a qualitative research with 18 life stories of students from different socio-economic backgrounds and with diverse sexual orientations. Results. According to the middle-range theory of transitions, sexual debut can be considered a developmental transition. The initiative can be their own, motivated by desire, or coerced by pressure from a partner or peers in which case underlay power relations either by age or hierarchy. Its features are shaped by the individual´s abilities, knowledge, and uncertainties, as much as by the circumstances surrounding the event and the socio-cultural precepts towards the topic. It is valued as a healthy transitional process when it is agreed upon by both members of the couple, planned and flows into symmetrical relations. Conclusion. The theory of transitions and analysis of the context are useful in understanding the phenomenon because the subjective experience is framed within normative, appreciative, and socio-cultural constructions. Nursing, as discipline, requires elements like those provided by this research to interpret the dynamics, meanings, as well as subjective and social processes in the sexual evolution of people in different contexts and historical moments.